2018
DOI: 10.1161/circgen.118.002107
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Left Atrial Gene Expression Yields Insights into the Genetic Susceptibility for Atrial Fibrillation

Abstract: Background Genome wide association studies have identified 23 loci for atrial fibrillation (AF), but the mechanisms responsible for these associations, as well as the causal genes and genetic variants, remain undefined. Methods and Results To identify the effect of common genetic variants on gene expression that might explain the mechanisms linking genome wide association loci with AF risk, we performed RNA sequencing of left atrial appendages from a biracial cohort of 265 subjects. Combining gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 32 publications
3
69
0
1
Order By: Relevance
“…Our previous eQTL analysis indicated that rs1152591, the top AF GWAS SNP at this locus, was a strong eQTL for SYNE2 expression at the gene level (p=6.13E-17) 4 . Here we performed transcript-level analysis, and we found that the linked SNPs rs1152595 and rs1152591 were the top two significant eQTLs for the SYNE21 isoform, and our reporter gene transfection showed that the risk alleles of both SNPs decreased enhancer and/or promoter activities, suggesting that these two eQTL SNPs regulate SYNE21 expression, and thereby play a role in the AF susceptibility.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Our previous eQTL analysis indicated that rs1152591, the top AF GWAS SNP at this locus, was a strong eQTL for SYNE2 expression at the gene level (p=6.13E-17) 4 . Here we performed transcript-level analysis, and we found that the linked SNPs rs1152595 and rs1152591 were the top two significant eQTLs for the SYNE21 isoform, and our reporter gene transfection showed that the risk alleles of both SNPs decreased enhancer and/or promoter activities, suggesting that these two eQTL SNPs regulate SYNE21 expression, and thereby play a role in the AF susceptibility.…”
Section: Discussionmentioning
confidence: 91%
“…AF associated rs1152591 and rs1152595 are eQTLs for SYNE21, a short mRNA isoform 235 LAA tissues were obtained during cardiac surgery from subjects of European ancestry and 30 self-reported African Americans, the clinical characteristics were reported in our previous study 4 . In that study, we performed a gene-level transcriptome analysis and we found that the AF GWAS SNP rs1152591 was a strong cis-eQTL for SYNE2 gene expression (q=6.7E-17) 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographics of this population were previously published. 4 Total RNA was isolated for subsequent sequencing analysis. These methods are detailed in our prior publication.…”
Section: Human Left Atrial Tissue Samples and Processingmentioning
confidence: 99%
“…Our prior expression quantitative trait locus (eQTL) study utilized next generation RNA sequencing (RNAseq) and single nucleotide polymorphism (SNP) genotyping in human left atrial appendages to identify the cis genes whose expression are associated with the top SNP at the AF GWAS loci. 4 We identified FAM13B as the gene whose expression is associated with the top GWAS SNP at chr. 5q31.…”
mentioning
confidence: 99%